Systematic review of gastrostomy complications and outcomes in pediatric cancer and bone marrow transplant. (10th July 2021) - Evans, James; Gardiner, Breeana; Green, Dan; Gibson, Faith; O'Connor, Graeme; Lanigan, Julie
Abstract: Background: Nutrition support is essential in children with cancer, including those undergoing bone marrow transplant (BMT), to reduce the risk of malnutrition and associated deleterious outcomes. Enteral nutrition is more commonly provided via nasogastric than gastrostomy tubes because of safety concerns with the latter in immunocompromised children. This systematic review investigated the incidence and type of complications and outcomes in pediatric cancer patients fed by gastrostomy. Methods: Databases were searched for randomized and observational studies investigating the use of any gastrostomy device in children aged <18 years with any cancer diagnosis, including those undergoing BMT. Five cohort and 11 case series studies were included. Owing to clinical heterogeneity, meta‐analyses were not performed. Results: Quality of evidence varied, with five studies judged at serious risk of bias and poor quality; however, the remaining 11 were considered to range from moderate to good quality. Across studies, 54.6% of children developed one or more complications, of which 76.6% were classified as minor, 23.4% major. The most frequent complications included inflammation (52% of episodes), infection (42.1%), leakage (22.3%), and granuloma (21%). Evidence regarding infection rates in cancer/BMT patients compared with other disease states was inconclusive. Gastrostomy feeding was associated with improvement or stabilization of nutrition status in 77%–92.7% of children. Conclusion: Gastrostomy feeding in this population is relatively safe and effective in stabilizing or improving nutrition status throughout treatment. Complications are frequent but mostly minor. Placement requires careful consideration of the complications, benefits, nutrition risk and status at diagnosis, and quality of life.